Fourth Child - Hall, Megan (Book collections on Project MUSE., 2008)
Megan Hall's first collection of poems, Fourth Child, has the texture of a carefully wrought, hand-stitched garment. It is something you want to bury your face in, like the familiar scented fabric of an item of clothing that belonged to a beloved who is gone. The Poems combine a dark humour and terrible grief with a lightness and restrained sensuality. Her language has the qualities of dance: uninhibited and polished, accomplished and vivid. Fourth Child shows a poet courageously facing deep feelings while being committed to accurate writing, making beautiful and living things out of the fabri.